INFLUENCE OF POLYOLS STRUCTURALLY BASED ON GLYCEROL, ETHYLENE- AND PROPYLENGLYCOLS ON FREE RADICAL OXIDATION IN RAT ORGANISM - Resunenko, Y.K.; Prokopov, V.A.; Zhukov, V.I. (World of Medicine and Biology, 2012)
The present work investigated activities of protein oxidative modification and lipid peroxidation at conditions of prolonged action of industrial chemical polluters e.g. polyols in 1/10 and 1/100 LD50. The research is a part for establishing biological action mechanism of the compounds. Polyols structurally based on glycerol (P-1103K, P-3003), ethylene- and propylenglycol (P-1601B, P-3502) increase in rat blood serum levels of aliphatic ketodinitrophenylhydrozones of neutral and alkaline characters, dienic conjugates, TBA-active products and Schiff’s bases on the 30th day of the compound peroral action. The most pronounced alteration were observed in 1/10 LD50. The displayed impairments must be considered when elaborating the prognosis of unfavorable influence of the substances on the population health.
Keywords: polyols; warm-blooded animals; oxidative modification of proteins; lipid peroxidation